Pengaruh Lama Fiksasi Neutral Buffered Formalin 10% Terhadap Kualitas Hasil Pewarnaan Hematoksilin Eosin Jaringan Mioma Uteri di RSUD Wangaya - Ketut Devita; Anak Agung Ayu Eka Cahyani; Putu Gede Subhaktiyasa (Program Study of Medical Laboratory Technology , Politeknik Bina Husada Kendari, 2026)
Uterine fibroids are benign tumors originating from the smooth muscle of the uterus, and their diagnosis can be established through histopathological examination using Hematoxylin and Eosin (H&E) staining. One of the important stages in tissue preparation is the fixation process using 10% Neutral Buffered Formalin (NBF), as the duration of fixation may affect the quality of tissue staining. This study aimed to determine the effect of 10% NBF fixation duration on the quality of Hematoxylin and Eosin (H&E) staining in uterine fibroid tissue with fixation times of 12, 24, and 48 hours.This study employed an analytical experimental design and was conducted at Wangaya Regional General Hospital from January to February. Data were analyzed using the Shapiro–Wilk normality test, which showed that the data were not normally distributed; therefore, the Kruskal–Wallis test was subsequently performed. The results showed a p-value of 0.006, indicating a significant difference among the groups. Post hoc analysis using the Mann–Whitney test demonstrated significant differences between the 12-hour and 24-hour fixation groups (p = 0.047) and between the 12-hour and 48-hour fixation groups (p = 0.007), whereas no significant difference was found between the 24-hour and 48-hour fixation groups. The results indicate that the duration of 10% NBF fixation affects the quality of Hematoxylin and Eosin (H&E) staining in uterine fibroid tissue, in which fixation for 24–48 hours provides better staining quality than fixation for 12 hours. This study is expected to serve as a reference for determining tissue fixation duration in routine histopathological examinations and for further research regarding tissue fixation processes and the quality of Hematoxylin and Eosin (H&E) staining. Keywords: Fixation Time, 10% Neutral Buffered Formalin, H&E Staining.